Structure and Optical Properties of BhSe3 Thin Films Prepared by Chemical Bath Deposition Method - Musa, A. H; AL-Homrany, A.M.J (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Thin films of BhSe3 have being deposited on glass substrates of about 80 - 172 Â± 14 nm thickness from an aqueous solution bath at temperature 293 K for period 0.5 to 6.0 hours using alchemical bath deposition method . The films are characterized by X-ray diffraction, X-ray florescent techniques and optical transmittance spectra measurements in the rang 350 - 400 nm at 293 K. And shows that as deposited films are amorphous and a transition to polycrystalline state has taken place after annealing them at 373 K, for 30 minutes, But they will be dan1aged at 423 K, for the above period. The optical band gab of the films have been found about 1.55 to 1.50 eV as deposited time is increased from 0.5 to 6.0 hours with a direct allowed type transition. 2 ml. of hydrazine hydrate is added to the aqueous solution bath, the thickness of the deposited films is found to increase continuously with an increase in dipping period up to 6 hours and it lead to decrease the deposition time for obtaining a sample of special thickness. Also the magnitude of band gap is decrease to 1.41-1.38 eV for the above periods of time.